2016
DOI: 10.3329/ptcb.v25i2.26255
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Total Phenolic Contents and Antioxidant Activity of Carrot Callus Extracts as Affected by Phenylalanine Precursor

Abstract: Carrot (Daucus carota) is a valuable plant with both therapeutic and horticultural potential. Stem, petiole and root derived calli of carrot were obtained on solid MS supplemented with 1 mg/l BAP + 2 mg/l NAA. Callus cultures supplemented with different L-phenylalanine (PHE) concentrations under light and dark conditions were evaluated for their antioxidant activity and total phenolic contents. The authors showed that PHE supplementation in Daucus carota cultures was necessary to raise the extraction yield per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…Our findings (Table 3) are in line with the results reported earlier by Arafa et al (2015) and Arafa and Aly (2018), who detected that the highest scavenging activity values in calli of stem, root, and petiole explants of Daucua carota L. carota was recorded with using phenylalanine as amino acid precursor and Bemani et al (2012) who increased more amounts of Taxol and antioxidant activity by increment of phenylalanine supply in the extract of suspension-cultured hazel (Corylus avellana L.) cells. Furthermore, our investigations are in partial harmony with those of Ghasemzadeh et al (2012) who reported that SA improved the production of some chemical structures such as fisetin and anthocyanin who possess more potency as antioxidant activity than the control in ginger varieties and Hadian-Deljou et al (2017) who attained more total phenolics and antioxidant activity by salicylic acid application using 2 mM concentration at the earlier stages of cold storage and using 1 mM concentration at the end of cold storage for red delicious apples.…”
Section: Evaluation the Percentage Of Free Radical Scavenging Capacitsupporting
confidence: 92%
“…Our findings (Table 3) are in line with the results reported earlier by Arafa et al (2015) and Arafa and Aly (2018), who detected that the highest scavenging activity values in calli of stem, root, and petiole explants of Daucua carota L. carota was recorded with using phenylalanine as amino acid precursor and Bemani et al (2012) who increased more amounts of Taxol and antioxidant activity by increment of phenylalanine supply in the extract of suspension-cultured hazel (Corylus avellana L.) cells. Furthermore, our investigations are in partial harmony with those of Ghasemzadeh et al (2012) who reported that SA improved the production of some chemical structures such as fisetin and anthocyanin who possess more potency as antioxidant activity than the control in ginger varieties and Hadian-Deljou et al (2017) who attained more total phenolics and antioxidant activity by salicylic acid application using 2 mM concentration at the earlier stages of cold storage and using 1 mM concentration at the end of cold storage for red delicious apples.…”
Section: Evaluation the Percentage Of Free Radical Scavenging Capacitsupporting
confidence: 92%
“…Regarding the HPLC analysis, 3-Hydroxy-4-methoxycinnamic acid, was appeared to be the main phenolic acid in callus infusion, this result is consistent with the findings of Arafa et al (2015) and Azeez et al (2017). These authors have reported that it is the major compound of callus produced under in vitro conditions.…”
Section: Discussionsupporting
confidence: 85%
“…According to the data obtained by us, in tea callus cultures grown on the main medium and on media with various precursors, it was PhA that caused rapid activation of their accumulation and the effect remained throughout the cultivation period ( Figure 2 ). The stimulating effect of this precursor on the PCs formation has been repeatedly noted for various plant objects [ 54 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 90%